1998
DOI: 10.1038/4350
|View full text |Cite
|
Sign up to set email alerts
|

The tomato Mi-1 gene confers resistance to both root-knot nematodes and potato aphids

Abstract: Mi-1, a Lycopersicon peruvianum gene conferring resistance to the agricultural pests, root-knot nematodes, and introgressed into tomato, has been cloned using a selective restriction fragment amplification based strategy. Complementation analysis of a susceptible tomato line with a 100 kb cosmid array yielded a single cosmid clone capable of conferring resistance both to the root-knot nematode Meloidogyne incognita and to an unrelated pathogen, the potato aphid Macrosiphum euphorbiae. This resistance was stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
179
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(189 citation statements)
references
References 23 publications
2
179
0
2
Order By: Relevance
“…Although few R genes have been shown to be induced upon pathogen infection, R gene related ESTs have in some cases been identiWed only in pathogen challenged libraries (Ronnings et al 2003). Transcription levels of the target genes are therefore expected to be low, which could lead to problems related to PCR kinetics and sensitivity (Vos et al 1998). However, when using the standard NBS proWling protocol as developed by van der Linden et al (2004), between 20 and 35 fragments were ampliWed, which is approximately half the number of bands typically ampliWed with NBS proWling on genomic DNA, suggesting that NBS proWling is suitable to analyse the expression of relatively low expressed genes, although further exploration of the limits of detection of NBS proWling, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although few R genes have been shown to be induced upon pathogen infection, R gene related ESTs have in some cases been identiWed only in pathogen challenged libraries (Ronnings et al 2003). Transcription levels of the target genes are therefore expected to be low, which could lead to problems related to PCR kinetics and sensitivity (Vos et al 1998). However, when using the standard NBS proWling protocol as developed by van der Linden et al (2004), between 20 and 35 fragments were ampliWed, which is approximately half the number of bands typically ampliWed with NBS proWling on genomic DNA, suggesting that NBS proWling is suitable to analyse the expression of relatively low expressed genes, although further exploration of the limits of detection of NBS proWling, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For some R genes, for example Mi, it was found that the same R gene confers resistance against diVerent pathogens (Vos et al 1998, Nombela et al 2003 implying that R genes can function in diVerent tissues. This assumption is supported by the Wndings of van der Vossen et al (2000) who reported about a resistance-gene cluster in potato containing genes with high homologies, but resistance to distinct pathogens aVecting diVerent plant tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), potato aphid (Macrosiphum euphorbiae), and sweetpotato whitefly biotypes B and Q (Bemisia tabaci ;Milligan et al, 1998;Rossi et al, 1998;Vos et al, 1998;Nombela et al, 2003). The gene encodes a classical resistance (R) protein homologous to proteins conferring resistance against viruses, bacteria, and fungi .…”
mentioning
confidence: 99%
“…But it was found later that the Mi gene also conferred resistance to the sucking insect aphid Macrosiphum euphorbiae. Thus, the Mi gene in tomato has dual specificity, showing resistance to both root knot nematodes and potato aphids (Rossi et al, 1998;Vos et al, 1998).…”
Section: Discussionmentioning
confidence: 99%